Using artificial intelligence for English language learning: Saudi EFL learners’ opinions, attitudes and challenges - Jamshed, Mohammad; Alam, Iftikhar; Sultan, Sultan Al; Banu, Sameena (Journal of Education and e-Learning Research, 2024)
The study investigates EFL (English as a Foreign Language) learners’ opinions, attitudes and the challenges of incorporating AI-powered teaching and learning. It also examines how their ideas and attitudes are affected by demographic variables. 258 students were selected using a random sampling method from a population comprising students studying in different levels of programs at the College of Science and College of Business Administration, Prince Sattam bin Abdul-Aziz University, KSA. A questionnaire was self-developed using some modified items from prior studies as the study looks at how certain independent variables (e.g., study level, residential background and parents’ educational level) affect the dependent variable (e.g., learners’ opinions, attitudes and challenges for AI-powered learning and teaching). The quantitative approach (descriptive quantitative design) revealed that Saudi EFL students held a high level of positive opinions and attitudes towards AI-powered learning. However, the analysis found that many students thought implementing AI-powered learning was challenging. A one-way ANOVA showed no significant difference based on respondents’ residential background and parental education. However, respondents differed significantly based on their level or year of study. The study findings will assist administrators and course teachers in using AI-powered technologies to overcome challenges and prepare students for achievement in the English language.